Quran in the Digital Age - Achmad Tifaza Alfarizi; Munir; Rizki Farabi (Penerbit Hellow Pustaka, 2024)
In the rapidly developing digital era, the Al-Quran cannot be separated from its impact. Technological transformation has brought new challenges and opportunities for the dissemination, understanding and application of the Koran in everyday life. This article explores the significant changes that have occurred in the way the Koran is accessed, studied, and practiced in a digital context. First, this article identifies technological developments that influence how to access the Koran, such as mobile applications, websites and social media. Second, challenges such as misuse of information and loss of a sense of emotional connection to sacred texts are discussed in this digital context. Third, this article highlights new opportunities, such as online learning platforms and interactive applications that facilitate deeper understanding of the Koran. By analyzing these transformations, challenges and opportunities, this article concludes the importance of awareness of the use of technology in religious contexts, as well as the need for a balanced approach between tradition and innovation to ensure there remains respect for the Koran in the digital era